Thermography and thermal image processing with data management - Toh, Hao Xiang (2018)
Tumours occurring post-reconstruction surgery is one of many challenges faced by plastic surgeons. Thermographic examination is one of the few imaging examination solutions that was introduced to detect the level of flap perfusion that helps to further minimize the complication. For patients that experience cancerous breast resection, one of the issues in plastic surgery is tissue restoration. Using unipedicular skin flap transplant on the specific area is the most prominent technique for such restoration. Despite the advancement of medical technology, marginal flap may still occur which leads to poor diagnosis. Here, thermographic examination is explored to determine the degree of flap perfusion, minimizing the complications. It is well-established in thermographic examination that subtraction-based image manipulation is executed post external cooling removal to reinforce the trait differentiation of the acquired thermal image. Studies will be done on the effect on skin rewarming after removing the cooling process on the outer skin, which will display the impact of blockage of blood flow more clearly. By using external cooling, a transit time method-based blood flow velocity estimation is done. It is evident that an external cooling based active thermography method can be used as a diagnosis tool for superficial blood vessel diseases based on the outcome acquired.